To What Extent Are Multiword Sequences Associated With Oral Fluency?. Issue 2 (31st December 2019) - Tavakoli, Parvaneh; Uchihara, Takumi
Abstract: This study examined the relationship between oral fluency and use of multiword sequences (MWSs) across four proficiency levels (Low B1 to C1 of the Common European Framework of Reference). Data came from 56 learners taking the speaking test of the Test of English for Educational Purposes, and our analysis obtained different measures of fluency (speed, breakdown, repair) and MWSs (frequency, proportion, association). Results showed that (a) high‐frequency n‐grams correlated positively with articulation rate; (b) n‐gram proportion correlated negatively with frequency of mid‐clause pauses; and (c) n‐gram association strength correlated positively with frequency of end‐clause pauses and negatively with repair frequency. Qualitative analysis suggested that the test‐takers borrowed some task‐specific n‐grams from the task instructions and used them frequently in their performance. Whereas lower proficiency speakers used these n‐grams verbatim, C1 level speakers used them competently in a variety of forms. We discuss significant implications of the findings for phraseology and language testing research. Abstract :